The rs1127354 Polymorphism in ITPA Is Associated with Susceptibility to Infertility - Mollaahmadi, Fahimeh (Cell J, 2018)
OBJECTIVE: Infertility is a common human disorder which is defined as the failure to conceive for a period of 12 months without contraception. Many studies have shown that the outcome of fertility could be affected by DNA damage. We attempted to examine the association of two SNPs (rs1127354 and rs7270101) in ITPA, a gene encoding a key factor in the repair system, with susceptibility to infertility. MATERIALS AND METHODS: This was a case-control study of individuals with established infertility. Blood samples were obtained from 164 infertile patients and 180 ethnically matched fertile controls. Total genomic DNA were extracted from whole blood using the standard salting out method, and stored at -20˚C. Genotyping were based on mismatch polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method in which PCR products were digested with the XmnI restriction enzyme and run on a 12% polyacrylamide gel. RESULTS: All genotype frequencies in the control group were in Hardy-Weinberg equilibrium. A significant association (in allelic, recessive and dominant genotypic models) was observed between infertile patients and healthy controls based on rs1127354 (P=0.0001), however, no significant association was detected for rs7270101. Also, gender stratification and analysis of different genotype models did not lead to a significant association for this single- nucleotide polymorphis (SNP). CONCLUSION: ITPA is likely to be a genetic determinant for decreased fertility. To the best of our knowledge, this is the first report demonstrating this association, however, given the small sample size and other limitations, genotyping of this SNP is recommended to be carried out in different populations with more samples.